Nutritional Status of Resident Female Orphans of Selected Orphanages of Dhaka City - Hussain, Mahnaz; Hossain, AMM Mokkaram; Bhuyan, Animul Huq (Journal of Bangladesh Society of Physiologist, 2011)
Background: Malnutrition specially under nutrition has been recognized as the major cause of morbidity and mortality among children. The orphan children are the most vulnerable section to malnutrition in our society. Objective: To assess the nutritional status in relation to anthropometrical measurements, hemoglobin level & clinical presentations of orphans of Dhaka City. Method: This nutritional survey was done under the supervision of Department of Nutrition, Institute of Nutrition and Food Science, Dhaka from November 2007 to January 2008. Total 179 female resident orphans aged 6-15 years from 2 orphanages named Alnahian Shishu Paribar and Ahsania Mission of Dhaka city were screened. They were assessed for BMI, Hb conc. and various clinical presentation of nutritional disorders. Data were analyzed by proportion test. Results: 60.3% of the total respondent’s from both orphanages were below the standard BMI which was significantly higher p<0.001) than that of 34.6% respondents with normal BMI. The malnourished orphans were 63.2% in Ahsania Mission and 58.3% were in Alnalian Shishu Paribar Etimkhana. Mean ±SD haemoglobin level of 116 children was 10.67 ± 1.37. 59.8% children had hemoglobin level less than 12.0g/dl and they were significantly higher than non anemic children (P<0.001). In Alnahian Shishu Paribar, 58.3% respondants were malnourished, 49% were anemic, 1.9% orphan had goiter, 91.3% were suffering from respiratory tract infection, 3.9% had xeropthalmia, 18.4% were suffering from angular stomatitis, 29.1% had cheliosis, 58.3% had glossitis, 1.9% had kwashiorkor and 1% were marasmic compared to those of 63.2%, 28.9%, 2.6%, 84.2%, 1.3%, 17.1%, 26.3%, 44.7%, 2.6%, 2.6% respectively in respondents of Ahsania Mission. The frequency of the deficiency diseases was almost similar in the two orphanages except anemia which was significantly higher in Ahsania Mission compared to that of Al Nahian. Conclusion: Significant percentage of orphans were undernourished and were suffering from various nutritional deficiency related disorders in both the etimkhaha & anemia was predominant in Ahsania Mission. Key words: malnutrition; BMI; Hb; anemia; orphan DOI: 10.3329/jbsp.v5i2.6779 J Bangladesh Soc Physiol. 2010 December; 5(2): 66-70